Behavioral Intention of Generation Y and Users’ Acceptance on Social Networking Website - Yeo, Wee Jiet (2013)
Due to the advanced technology, distance is not a problem to stop people from connecting with one each other. Through the social networking websites (SNWs), it enables people around the world to stay connected, build and strengthen the relationship. Different people have different behavioral intentions of using SNWs. The reasons that encourage the users to use SNWs may include perceived usefulness, perceived ease of use and perceived enjoyment. However, privacy concern will negatively impact the users’ behavioral intention in using the SNW. Therefore, the purpose of this research is to investigate the privacy concern and behavioral intention of users in acceptance on social networking websites. In addition, it examines the relationship between perceived usefulness, perceived ease of use, perceived enjoyment and users’ behavioral intention in using social networking websites. This research will focus on generation Y who are the technology-driven people and actively accessing to SNWs. A quantitative research method will be used for this research which is conducts survey through questionnaire. The questionnaires will be distributed to 450 students who are generation Y study at Institution A that located at Negeri Sembilan, Malaysia. In order to analyze the data, Statistical Package for Social Science (SPSS) and Partial Least Square (PLS) will be used as the analysis technique. The findings of this research will provide empirical evidence to SNW operators, application developers, marketers, other parties in managing their businesses in the context of SNW and help them to develop strategies in order to increase users’ acceptance on SNWs.